Factors Influencing Step Ablation in the Expansion Section of a Composite Nozzle in a Solid Rocket Motor - Jiming Cheng; Chunyu Zhang; Hang Yan; Xiping Feng; Guoqiang Zhu (Aerospace, 2025)
During the operation of a solid rocket motor, the nozzle, which is a key component, is subjected to extreme conditions, including high temperatures, high-speed gas flow, and discrete-phase particles. For composite nozzles incorporating a carbon/carbon (C/C) throat liner and a carbon/phenolic expansion section, thermochemical ablation and the formation of ablation steps during the ablation process significantly hinder nozzle performance and engine operational stability. In this study, the fluid and solid domains and the physicochemical interactions between them during nozzle operation were analyzed. An innovative thermochemical ablation model for composite nozzles was developed to account for wall recession. The coupled model covered multi-component gas flow, heterogeneous chemical reactions on the nozzle surface, structural heat transfer, variations in material parameters induced by carbon/phenolic pyrolysis, and the dynamic recession process of the nozzle profile due to ablation. The model achieved coupling between gas flow, heterogeneous reactions, and structural heat transfer through interfacial mass and energy balance relationships. Based on this model, the distribution of the nozzle’s thermochemical ablation rate was analyzed to investigate the mechanisms underlying ablation step formation. Furthermore, detailed calculations and analyses were performed to determine the effects of the gas pressure, temperature, H2O concentration, and aluminum concentration in the propellant on the ablation rate of the throat liner and the thickness of the ablation steps. This study provides a theoretical foundation for the thermal protection design and performance optimization of composite nozzles, improving the reliability and service life of solid rocket motor nozzles and advancing technological development.